Contributions of Parenting Sense of Competence to Family Functioning in a Sample of Military-Connected Families Living in the Community. (October 2019) - Makhija, Nita J.; Ohye, Bonnie Y.; Zakarian, Rebecca J.; Jakubovic, Rafaella J.; Bui, Eric
The purpose of this investigation was to examine the potential contributions of parenting sense of competence and parental psychological symptoms to family functioning in a sample of military-connected families attending public elementary school. Fifty-six parents (61.8% female; 92.9% White; 5.3% Hispanic; mean age = 38.5, SD = 7.03) completed the Depression, Anxiety, and Stress Scale (DASS), the Parenting Sense of Competence Scale (PSOC), and the General Functioning Scale of the Family Assessment Device (GF-FAD). Participants' GF-FAD scores negatively correlated with their PSOC scores ( r = −.48, p < .001). A negative trend between the PSOC scores and DASS scores is observed ( r = −.25 p < .06). A multiple regression analysis indicates that both scores on PSOC (β = −.46, p < .001) and DASS (β = 0.3, p = .01) were independently associated with the GF-FAD scores. These results suggest that among military families, a sense of efficacy as a parent may influence family functioning above and beyond the effect of parental distress and that interventions designed to promote sense of parenting competence may improve military family functioning through a process different than that of interventions to alleviate psychological distress.